Peningkatan Mutu Guru Sekolah Menengah Kejuruan Melalui Penerapan Supervisi Akademik di SMKN 4 Kota Bengkulu - Paidi Paidi; Adisel Adisel (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the improvement of the quality of vocational school teachers through the application of academic supervision. In order to determine the success of the implementation of school supervision, this research was carried out using qualitative research methods located at SMKN 4 Bengkulu City. The number of research respondents was 64 teachers spread over the Information and Communication Technology (ICT) expertise program, Automotive and Maritime Engineering. Supervision results show that the achievement of content standard mapping is 100%, indicator development is 100%, syllabus development is 100%, lesson plans are prepared 90%, KKM document is 100%, learning media use is 100%, application learning methods is 75%, use learning resources is 100%, 100% use and assessment techniques, 100% learning outcomes analysis, 75% ICT utilization and 80% learning completeness analysis. The results of the teacher competency assessment ranged from 71.70. The conclusion of this research is that the implementation of learning administration by the teachers of SMKN 4 Bengkulu City is quite good and the average value of the teacher's performance is also quite good. Keywords: School action research, supervision and vocational school